Desain Alat Smart Farming Penyiram Bawang Merah Menggunakan Arduino Uno Berbasis Android - Novta Dany’el Irawan; Shafiq Nurdin; Muhammad Athoillah; Riski Nur Istiqomah Dinnullah (P3M Politeknik Negeri Cilacap, 2022)
One of the technological developments in agriculture is smart farming. Shallot farmers still carry out the process of watering shallot plants manually. This takes a long time because farmers have to go around the agricultural land during the watering process. To solve these problems, an automatic shallot sprinkler machine was designed that can be applied by farmers. The Arduino Uno ATMega328 microcontroller is used on this machine as the control system, while Android is used for the interface. The android interface on this machine can provide a graphical display, therefore farmers can give direct orders to drive a DC motor (Direct Current) and a DC pump on/off switch (Direct Current). The results of the smart farming research on this automatic onion sprinkler help farmers get 72% efficient time. The comparison can be seen in the manual watering process on 10,000m2 agricultural land that takes 7 days, on the other hand, it only takes 2 days when it is done with smart farming technology.